2012
DOI: 10.1590/s0101-20612012005000085
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of tempeh from soybean cultivars specially developed for human consumption

Abstract: Tempeh is a food obtained by fermentation of soybean grains by the fungus Rizophus oligosporus. It is a traditional Indonesian food that presents benefits for human health protecting against diarrhea and chronic diseases. Tempeh processing includes dehulling, cooking, inoculation, and fermentation. In this study, chemical characteristics of tempeh prepared with soybean cultivars specially developed for human consumption (BRS 216, BRS 232, BRS 257, and BRS 267) were investigated. Soybean grains and tempeh obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 20 publications
1
20
1
4
Order By: Relevance
“…Tempeh was prepared according to the traditional method (BAVIA et al, 2012). After initial cleaning to remove foreign particles, dry and whole beans were mechanically peeled (brand MaqSoy).…”
Section: Methodsmentioning
confidence: 99%
“…Tempeh was prepared according to the traditional method (BAVIA et al, 2012). After initial cleaning to remove foreign particles, dry and whole beans were mechanically peeled (brand MaqSoy).…”
Section: Methodsmentioning
confidence: 99%
“…Perbedaan kadar air terjadi karena perbedaan penetrasi air ke dalam matriks biji dan perbedaan pengembangan biji. Kadar air tempe juga dipengaruhi oleh aktivitas pertumbuhan kapang dalam tempe (Astawan et al, 2013 4,0 3,5 4,0 3,5 4,0 3,0 Keterangan: 1) Menggunakan uji hedonik/ tingkat kesukaa skala 1-5, yaitu: 1=sangat tidak suka, 2=tidak suka, 3=agak suka; 4=suka, dan 5=sangat suka 2) Menggunakan uji skoring skala 1-5, yaitu: 1=sangat lunak, 2=lunak, 3=sedang, 4=keras, dan 5=sangat keras; diuji dibandingkan dengan kotiledon bijinya yang dapat disebabkan oleh hilangnya beberapa komponen terlarut seperti gula dan mineral dari biji kedelai (Bavia et al, 2012), aktivitas proteolitik miselium kapang (Rahayu 2004), dan peningkatan jumlah nitrogen terlarut dan asam amino bebas dalam tempe karena digunakan oleh kapang Rhizopus sebagai sumber N untuk pertumbuhannya (Astuti et al, 2000).…”
Section: Varietasunclassified
“…Despite exhibiting poor growth performances, positive results in FCR, PER and NPU indicate that fish were able to utilized nutrients in TMP better than fish fed with unfermented SBM. Several studies have reported that soluble protein, glucose, free amino acid content, vitamin and other nutrients increased sharply after fermentation and thus improving digestion and feed utilization [28,[32][33]36]. Yamamoto et al [31] reported that few studies showed nutritional value of SBM was able to improve through fermentation, though the effect on improvement of the growth performance was very limited as seen in present study.…”
Section: Discussionmentioning
confidence: 45%
“…Besides that, fermentation of soybean has been reported to be able to boost up non-specific immune system and prevent various physiological abnormalities in fish fed with diets containing fermented soybean (FSBM) [30][31]. These improvements in nutritional and functional properties of fermented soybean compare to unfermented soybean are probably due to the degradation of soybean allergens and antinutritional factors by microbial proteolytic enzyme and various treatments during fermented soybean production [28,[32][33].…”
Section: Evaluation Of Tempeh As a Potential Alternative Protein Sourmentioning
confidence: 99%